Neo-Tribes Consumption, Leisure and Tourism (Springer International Publishing, 2018)
This collection brings together perspectives drawn from a range of international scholars who have conducted research into the applications of neo-tribal theory. The concept of the neo-tribe was first introduced by the French sociologist Michel Mafessoli (1996) to describe new forms of social bonds in the context of late modernity. This book critically explores the concepts that underpin neo-tribal theory, using perspectives from different disciplines, through a series of theoretically informed and empirically rich chapters. This innovative approach draws together a recently emergent body of work in cultural consumption, tourism and recreation studies. In doing so, the book critically progresses the concept of neo-tribe and highlights the strengths, weaknesses and the opportunities for the application of neo-tribal theory in an interdisciplinary way.